Goal Selection and Goal Pursuit: The Role of Self-concordance and Implementation Intentions - Upadhyay, Satwik (My University, 2025)
The pursuit of long-term goals profoundly influences behaviour and life satisfaction, yet how individuals select these goals has largely remained underexplored in research. Current theories of goal-directed behaviour provide limited insight into how people actively seek goals or whether they wait for them to emerge. Additionally, individuals vary in their ability to choose goals that align with their true selves. Many pursue unfulfilling goals for years, often unaware of better-fit alternatives. Therefore, selecting self-appropriate goals is a skill, especially relevant in today's autonomous and gig work environment, driven by rapid technological disruptions resulting in a continuous upgrade of existing individual skills and learning. The present research investigates goal selection difficulties through the self-concordance framework, rooted in self-determination theory to support meaningful goal-setting. Complementary self-management techniques, such as implementation intentions, further enhance goal-relevant behaviour and well-being.
Tripathi, Nachiketa